Pendekatan Partisipatif dalam Pengabdian kepada Anak Sekolah Minggu dan Remaja Berbasis Ekologi di HKBP Pardamean Medan - Riana Lumban Raja; Futriana Purba; Marfina Kristin N. Naibaho; Naomi Christine Sijabat; Susi Santrika Sitinjak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service program aims to enhance ecological awareness among the congregation of HKBP Pardamean Medan through a participatory approach to environmental education. A qualitative method was applied by actively involving the congregation, particularly Sunday School children, in learning and environmentally friendly practices. The results indicate that the participatory approach effectively fosters ecological awareness in cognitive, affective, and behavioral dimensions through role modeling and active engagement. This program highlights the church’s strategic role in contextual faith formation and environmental responsibility.